230k views
1 vote
4. [0/2 Points]. DETAILS

(b) g(g(3))
Use f(x) = 5x - 4 and g(x) = 2x2 to evaluate the expression.
(a) f(f(2))
how do i solve this?

User Jos Vinke
by
7.4k points

1 Answer

5 votes

Answer:

324

Explanation:

To evaluate (a) f(f(2)), we first evaluate f(2) which is 52-4 = 6. Then, we evaluate f(6) which is 56-4 = 26. So, f(f(2)) = 26.

To evaluate (b) g(g(3)), we first evaluate g(3) which is 23^2 = 18. Then, we evaluate g(18) which is 218^2 = 324. So, g(g(3)) = 324

User Jamjam
by
7.2k points